The impact of DRG reimbursement system on appropriate techniques of traditional Chinese medicine—evidence from pilot cities with traditional Chinese medicine hospitals in China - Zhang, Jin; Zhou, Yana; Han, Dan; Zhang, Chen; Xiong, Yajuan (Frontiers in Health Services, 2025)
IntroductionGiven the ongoing development and significant medical role of Traditional Medicine Hospital (TCM) techniques in Chinese TCM hospitals, it is imperative to conduct an assessment on the influence of the gradual implementation of the DRG reimbursement system in W City's three public hospitals on the utilization of appropriate techniques of TCM.MethodsThis study uses the Difference-in-Difference method to analyze the economic impact of the DRG reimbursement system. It compares cost changes between the TCM techniques group and other groups before and after DRG implementation to reveal the actual influence on cost. Visualization tools show cost variations from 2019 to 2022, bolstering research credibility. A T-test analyzes cost disparities, validating prediction model accuracy. Finally, a parallel trend test ensures reliability of the DID model's results.Results(1)The total cost of appropriate techniques of TCM group decreased significantly (p < 0.001), with a 14.27% reduction in cost-effective TCM techniques (p < 0.001) but no significant changes in surgical cost.(2) Cost analysis of various TCM techniques showed significant decreases in total cost for external treatment and acupuncture, by 4.78% and 8.06% respectively (p < 0.001). cost for external treatment, orthopedic treatment, acupuncture, and special therapies also decreased by 13.67%, 14.27%, 16.8%, and 9.3% respectively (p < 0.001).(3)After analyzing 8 departments with high discharge rates, the total cost of TCM techniques in cardiology decreased by 18.86% (p < 0.001) under the DRG reimbursement system, while acupuncture cost increased by 11.85% (p < 0.001). In orthopedics, TCM techniques cost decreased by 30.3% (p < 0.001), but acupuncture and stomach/spleen departments saw significant increases of 18.88% and 46.66% respectively (p < 0.001).(4)Overall, there has been a significant reduction in the cost of TCM techniques following DRG payment reform. Notably, cost changes varied across departments, and acupuncture and moxibustion have experienced substantial cost fluctuations.ConclusionsThe DRG payment reform has had a significant impact on appropriate techniques of TCM utilization and medical expense control, reflecting hospitals’ strategic adjustment in balancing service quality with the DRG policy. It is recommended that policymakers consider the compatibility of DRG with TCM methods to ensure fairness and efficiency.